Construção e aplicação de uma sequência de ensino investigativo para o ensino de Botânica - Tognon, Michele Eidt (2019)
Considering the current scenario of Botany teaching in our country, its importance to the un-derstanding of natural phenomena, and to meet the demand for teaching focused on the under-standing of the nature of science, the assimilation of concepts and the understanding of the impacts of science and its technologies, it was developed a teaching resource in order to make the teaching of Botany more motivating and contribute to the Scientific Literacy of high school students. This study follows a quanti-qualitative approach and its methodological proposal is in accordance to a cognitive/cultural view of teaching. The study was carried out involving 3rd year students from the Dom Bosco Public School in Lucas do Rio Verde. There is a teaching potential in this didactic teaching in promoting advances to students´ scientific literacy. The implementation of the Investigative Teaching Sequence allowed students the possibility of dis-cussing, building concepts and the contact with the scientific method; to the researcher the im-plementation allowed the reflection about possible solutions concerning the role of elaborating investigative teaching strategies for students´ learning. It is believed that this research may con-tribute so that Biology teachers can identify methodological aspects that facilitate scientific literacy and the construction of knowledge in Botany. In addition, it is hoped that it may moti-vate teachers to develop their own “investigative teaching sequences” considering their local problems as starting points.